Ovarian fibrosarcoma : A Case Report - Syamel Muhammad; Reyhan Julio (Andalas Obstetrics And Gynecology Journal, 2023)
This case report aims to report and discuss cases of ovarian fibrosarcoma. Ovarian fibrosarcoma is a rare casethat generally occurs in women who have menopause. In the case of ovarian fibrosarcoma, the patient was 43years old, had two children, and had no complaints during menstruation. The patient has lost weight in the lastsix months. The patient has performed debulking surgery optimally. On the PA results, it looks macroscopic, apiece of brownish-white tissue, densely rubbery, with a size of 15x12x5 cm, a solid white part is visible, and thereis a yellowish-white part and anger, there is a 0.5-1.5 cm cavity filled with a yellowish liquid. On microscopicexamination of the tumor, the tissue section appears to consist of a diffuse proliferation of tumor cells withhypercellular and hypocellular areas. Based on the results of macroscopic and microscopic examination of thetumor tissue, a skewed sarcoma is established in fibrosarcoma. The patient underwent chemotherapy after tumorsurgery. Although there is no clear consensus on the administration of fibrosarcoma chemotherapy, severalpublished case reports have demonstrated a lower probability of recurrence and a better prognosis in patientsundergoing chemotherapy.